User Orientation Maps: An Approach to Address User Diversity in Design for Sustainable Behaviour. (2nd January 2017) - Coskun, Aykut; Erbug, Cigdem
Abstract: There has been an increasing tendency among design researchers to explore the potential of design to change user behaviour in the interest of sustainability. To date, numerous techniques have been proposed, aimed at providing more guidance to design researchers and practitioners on how to encourage sustainable behaviour. Choosing a technique suitable for both the target behaviour and the target user is a critical task when designing for sustainable behaviours. The influence of individual characteristics on user compliance with different techniques makes this task more compelling for designers. To make this task easier for them, we offer a new approach, called the 'user orientation map', to explore and represent user diversity by showing the range of user types and techniques to promote behavioural change for each user type. We illustrate this approach with a case study on eco-friendly driving, and identify nine user types.